2012
DOI: 10.1002/rmv.1718
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine kinase 1 in viral infections

Abstract: Sphingosine kinase 1 (SphK1) is an enzyme that phosphorylates the lipid sphingosine to generate sphingosine-1-phosphate (S1P). S1P can act intracellularly as a signaling molecule and extracellularly as a receptor ligand. The SphK1/S1P axis has well-described roles in cell signaling, the cell death/survival decision, the production of a pro-inflammatory response, immunomodulation, and control of vascular integrity. Agents targeting the SphK1/S1P axis are being actively developed as therapeutics for cancer and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 125 publications
2
28
0
Order By: Relevance
“…S1P may also influence dengue pathogenesis in other ways. S1P has important effects on immune cell migration, release of inflammatory mediators, phagocytosis and cell death, as reviewed by Carr et al 34 and Maceyka et al 35 Specific data concerning alterations in sphingolipid metabolism in dengue infection are scarce. In vitro, reduced SphK1 in dengue-infected cells showed enhanced TNF-a induced apoptosis, 24 which could limit severe complications induced by pro-inflammatory cytokines and limit ongoing viral replication within infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…S1P may also influence dengue pathogenesis in other ways. S1P has important effects on immune cell migration, release of inflammatory mediators, phagocytosis and cell death, as reviewed by Carr et al 34 and Maceyka et al 35 Specific data concerning alterations in sphingolipid metabolism in dengue infection are scarce. In vitro, reduced SphK1 in dengue-infected cells showed enhanced TNF-a induced apoptosis, 24 which could limit severe complications induced by pro-inflammatory cytokines and limit ongoing viral replication within infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus S1pr1-deficient megakaryocytes showed impaired migration of proplatelet extrusions in the circulatory compartment and impaired proplatelet shedding. Beyond that hematopoetic-specific knockout of S1pr1 leads to severe thrombocytopenia (19).In other cell types, S1P participates in the regulation of cell migration, proliferation, and cell adhesion (25, 37), as well as angiogenesis, atherosclerosis, and inflammation (11,23,37,43). Furthermore, S1P is heavily produced and secreted from activated platelets (53).…”
mentioning
confidence: 99%
“…In other cell types, S1P participates in the regulation of cell migration, proliferation, and cell adhesion (25, 37), as well as angiogenesis, atherosclerosis, and inflammation (11,23,37,43). Furthermore, S1P is heavily produced and secreted from activated platelets (53).…”
mentioning
confidence: 99%
“…9 SphK1 influences diverse cellular functions by regulating important cellular signaling pathways, including NF-kB, ERK/MAPK, and PI3K/ AKT. 2,[10][11][12] In addition, SphK1 is the predominant oncogenic isoform observed in human cancers 13,14 and its expression is elevated in stomach, lung, brain, colon, kidney, and breast cancers and non-Hodgkin lymphoma, 15 as well as in other cancers in which high tumor expression of SphK1 is correlated with decreased patient survival. [16][17][18] A recent report demonstrated that inhibition of SphK1 induced cell death in colon cancer cell lines and attenuated the serum-dependent PI3K/ AKT signaling and enhanced sensitivity of colon cancer cells to the chemotherapy drug, 5-fluorouracil.…”
Section: Introductionmentioning
confidence: 99%
“…POC, percent of control. Scatter plots comparing pIC 50 (-log10 [IC 50 ]) values determined from 10-point concentration-response testing of (A) 5,561 triaged IMAP HTS hits in SphK1 and SphK2 IMAP assays and (B) 78 selected IMAP HTS hits in SphK1 IMAP and microfluidic assays. The dashed lines show x = y. Potency of selected inhibitors and the optimized compound, C2, in the yeast and IMAP assays.…”
mentioning
confidence: 99%